2022
DOI: 10.1007/s00520-022-07462-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with head-lift exercise in head and neck cancer patients with dysphagia: results from a randomized, controlled trial with flexible endoscopic evaluation of swallowing (FEES)

Abstract: Background This randomized study aimed to evaluate the effects of the Shaker head-lift exercise (HLE) to improve dysphagia following oncologic treatment for head and neck cancer (HNC). Methods Patients with dysphagia following oncologic treatment for HNC were randomly assigned to intervention (n = 23) or control (standard dysphagia management, n = 24) groups. Swallowing was evaluated at baseline and at 8-week follow-up using flexible endoscopic eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The methodological quality of the studies included in our review was good (PEDro score = 6.38 out of 10, SD=1.09). During methodological quality assessment, 14 studies of good quality 45,47,48,[50][51][52][53][54][55][56]58,59,61,63 and 4 studies of acceptable methodological quality were identified 49,57,60,62 .…”
Section: Methodological Quality Assessment (Pedro Scale)mentioning
confidence: 99%
See 4 more Smart Citations
“…The methodological quality of the studies included in our review was good (PEDro score = 6.38 out of 10, SD=1.09). During methodological quality assessment, 14 studies of good quality 45,47,48,[50][51][52][53][54][55][56]58,59,61,63 and 4 studies of acceptable methodological quality were identified 49,57,60,62 .…”
Section: Methodological Quality Assessment (Pedro Scale)mentioning
confidence: 99%
“…The risk of bias of the included randomized clinical trials, as measured by the ROB 2.0 tool, can be marked as low to moderate risk of bias. When analyzing each bias, we found a high risk of bias related to the deviations from intended interventions in most of the included studies 45,47,48,[50][51][52][53][54][55][56][57][58][59][60][61][62][63] , mainly due to lack of blinding of participants and personnel. In relation to the selection of the reported outcomes 45,54,57,[59][60][61][62][63] , we detected a high risk of bias since the researchers did not report the outcome in the study variables in detail.…”
Section: Risk Of Bias Assessment (Rob 20)mentioning
confidence: 99%
See 3 more Smart Citations